Sustainable Business Insights from the Field of Sustainability Engineering - Taylor, Bruce (Taylor & Francis Group, 2025)
This book stands on the shoulders of sustainability engineering insights to identify blind spots in conventional business, engineering, and environmental school curricula that result in substantial missed opportunities
Description based on publisher supplied metadata and other sources